BURNOUT SYNDROME AMONG RESIDENTS OF A LARGE URBAN HOSPITAL - MAZHAR , H; SUBHAN , U; AKRAM , MH (Biological and Clinical Sciences Research Journal, 2023)
The questionnaire-based prospective study was conducted in Shifa Hospital, Islamabad, from January 2022 to July 2022, to evaluate the prevalence of burnout and its associated variables among residents of a major urban hospital in Pakistan. Residents in the hospital were sent a Google form, and their consent for inclusion in the study was taken. The prevalence of burnout was assessed using Copenhagen Burnout Inventory (CBI) scale. Results showed that 40 (60%) residents had a total burnout. 91 (60.6%) had personnel burnout, 66 (44%) had burnout due to interaction with patients, and 64 (42.6%) had occupational burnout. It was concluded that burnout syndrome is prevalent among doctors, and it is important to identify and address symptoms. Stress management strategies like psychological counseling and meditation should be available for residents.